Localização zonal e linear de vazamentos em tubulações industriais por emissão acústica - Bertolini, Diego Siedel (2024)
Anomalies in industrial pipelines cause environmental, social, and financial damage. For the detection and localization of these events, various techniques are available. Among them, Acoustic Emission (AE) stands out as a non-intrusive method with high sensitivity and precision. However, due to the high cost of this technique, its large-scale application is limited. There is, nevertheless, potential for the development of more economical solutions. The objective of this work is to develop an acquisition system composed of hardware and software for reading commercial AE sensors, allowing for zonal and linear leak localization. The adopted methodology involves filtering the leak signal and locating it in two stages. The first stage, called zonal localization, uses the Average Signal Level (ASL) and Root Mean Square (RMS) parameters, which are widely used in practice. The second stage, called linear localization, is based on the cross-correlation of the signals. For the construction of the device, GI40 AE sensors, a Printed Circuit Board (PCB), a USB oscilloscope Analog Discovery 2, and a Raspberry Pi 4 microcomputer were used. The experimental methodology included the use of a 90-meter-long industrial carbon steel pipeline with a diameter of 2 inches. To simulate a leak condition, a 1-meter spool with a 1 mm hole was inserted. For the largest sensor spacing (90 m), the absolute error was 3 m. The results of this study demonstrated that the developed system is capable of employing zonal and linear analyses to locate leaks according to the AE technique.